Endothelin‐1 enhances neutrophil adhesion to human coronary artery endothelial cells: role of ETA receptors and platelet‐activating factor - Zouki, Christine; Baron, Chantal; Fournier, Alain; Filep, János G (British journal of pharmacology, 1999)
The potent coronary vasoconstrictor, endothelin‐1 (ET‐1) may also regulate neutrophil traffic into tissues. The aim of the present study was to characterize the endothelin receptors responsible and to investigate the underlying mechanisms. ET‐1 (1 nM–1 μM) markedly enhanced attachment of human neutrophils to lipopolysaccharide‐, and to a lesser extent, to ET‐1‐activated human coronary artery endothelial cells (HCAEC). This can partially be blocked by monoclonal antibodies against E‐selectin, L‐selectin or CD18, whereas combination of the three antibodies inhibited adhesion by ∼83%. Increases in neutrophil adhesion evoked by ET‐1 were also blocked by the platelet‐activating factor (PAF) antagonists, BN 52021 (50 μM) and WEB 286 (10 μM). ET‐1 downregulated the expression of L‐selectin and upregulated expression of CD11b/CD18 and CD45 on the neutrophil surface and induced gelatinase release with EC50 values of ∼2 nM. These actions of ET‐1 were almost completely prevented by the ETA receptor antagonist FR 139317 (1 μM) and the ETA/ETB receptor antagonist bosentan (10 μM), whereas the ETB receptor antagonist BQ 788 (1 μM) had no effect. ET‐1 slightly increased the expression of E‐selectin and ICAM‐1 on HCAEC, that was prevented by BQ 788, but not by FR 139317. Receptor binding studies indicated the presence of ETB receptors (KD: 40 pM) on phosphoramidon‐treated HCAEC and the predominant expression of ETA receptors (KD: 38 pM) on neutrophils. These results indicate that promotion by ET‐1 of neutrophil adhesion to HCAEC is predominantly mediated through activation of ETA receptors on neutrophils and subsequent generation of PAF. British Journal of Pharmacology (1999) 127, 969–979; doi:10.1038/sj.bjp.0702593